Reception of Literary Legend "Si Losung and Si Pinggan Lake" in the Preservation of Local Wisdom - Sri Listiana Izar (Proceeding International Conference on Malay Identity, 2020)
This research on the literary reception of the legends of Lake Si Losung and Si Pinggan in the Defense of Wisdom is research on the responses of the people of Siponjot Village. The response from the people of Siponjot Village shows that after reading the text provided the researcher accepts and acknowledges the alignment of the contents of the text of the legend of Lake Si Losung and Si Pinggan in the Defense of Wisdom in accordance with the story that the community knows. From the results of the research, the community responds that there is a large and positive influence on society and some people can apply good values ??such as being honest and not imitating the character traits of Datu Dalu and Saahangmaima who are stubborn, liars, do not like to give in, arrogant and like to fight with each other. sibling. However, the people of Siponjot Village who believe in the legend of Lake Si Losung and Si Pinggan in the Defense of Wisdom really only come from the old group, while many young people still think that the story is just a myth. Apart from the legend of Lake Si Losung and Si Pinggan in Defense of Wisdom, the 10 people who were respondents hoped that the legend of Lake Si Losung and Si Pinggan in Defense of Wisdom could provide positive values ??for all people and apply them to themselves.Keywords: reception; literature; local culture; legend; defense